Sprint performance and propulsion asymmetries on an ergometer in trained high- and low-point wheelchair rugby players - Goosey-Tolfrey, V. L.; Vegter, R. J. K.; Mason, B. S.; Paulson, T. A. W.; Lenton, J. P.; van der Scheer, J. W.; van der Woude, L. H. V. (Scandinavian Journal of Medicine & Science in Sports, 2018)
The purpose of this study was to examine the propulsion asymmetries of wheelchair athletes whilst sprinting on an instrumented, dual-roller ergometer system. Eighteen experienced wheelchair rugby players (8 low-point (LP) (class =1.5) and 10 high-point (HP) (class =2.0)) performed a 15s sprint in their sports wheelchair on the instrumented ergometer. Asymmetry was defined as the difference in distance and power output (PO) between left and right sides when the best side reached 28m. Propulsion techniques were quantified based on torque and velocity data. HP players covered an average 3m further than the LP players (P=0.002) and achieved faster sprint times than LP players (6.95 ± 0.89 vs. 8.03 ± 0.68 s, P=0.005) and at the time the best player finished (5.96 s). Higher peak PO's (667 ± 108 vs. 357 ± 78 W, P=0.0001) and greater peak speeds were also evident were for HP players (4.80 ± 0.71 vs. 4.09 ± 0.45 m·s-1, P=0.011). Greater asymmetries were found in HP players for distance (1.86 ± 1.43 vs. 0.70 ± 0.65 m, P=0.016), absolute peak PO (P=0.049) and speed (0.35 ± 0.25 vs. 0.11 ± 0.10 m·s-1, P=0.009). Although HP players had faster sprint times over 28m (achieved by a higher PO), high standard deviations show the heterogeneity within the two groups (e.g. some LP players were better than HP players). Quantification of asymmetries is not only important for classifiers but also for sports practitioners wishing to improve performance as they could be addressed through training and/or wheelchair configuration.